La fundación del Studium Generale de Lleida y la tradición jurídica ilerdense. - BUSQUETA, JOAN J. (Scripta, 2020)
After some considerations on the relationships between the process of consolidation of an urban oligarchy, during the 13th century, and the foundation of the General Study, among other reasons given by hisotriography, we reflect, on this occasion, on the legal tradition, that would help define the foundational normative context, and, derived from this, the need and importance of that first Faculty of Law emerged in the Hispanic territories of the Crown of Aragon, as well as of the jurists who taught their lessons and of those who received them.